2020
DOI: 10.1111/aec.12858
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of targeted consumption of mosses by birds in sub‐Antarctic South America

Abstract: Bryophyte consumption is uncommon among bird species globally and is often presumed incidental. We sought to determine whether herbivorous bird species of the high Andes, including the white-bellied seedsnipe (Attagis malouinus) and Chloephaga geese (C. picta and C. poliocephala), consume bryophytes, and if so, how frequently. We collected 26 seedsnipe and 22 goose droppings from alpine and sub-alpine habitats of Navarino Island, Chile and examined their contents for bryophyte diaspores. We detected bryophyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Additionally, Willson, Traveset, and Sabag (1997) observed seeds of four fleshy‐fruit plants in faeces of upland goose and ashy‐headed goose ( Chloephaga poliocephala ) in Tierra del Fuego. Russo, Robertson, MacKenzie, Goffinet, and Jimenez (2020) found evidence that these geese species also disperse mosses by endozoochory. Silva et al.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Willson, Traveset, and Sabag (1997) observed seeds of four fleshy‐fruit plants in faeces of upland goose and ashy‐headed goose ( Chloephaga poliocephala ) in Tierra del Fuego. Russo, Robertson, MacKenzie, Goffinet, and Jimenez (2020) found evidence that these geese species also disperse mosses by endozoochory. Silva et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has attempted to cultivate fragments found in fecesin vitro with some success (Wilkinson et al, 2017;Russo et al, 2020). In this study, we partially followed Russo et al's (2020) fragment-processing methods.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research suggests that birds, such as mallard ducks (Anas platyrhynchos ) and sub-Antarctic geese and shorebirds, might be capable of dispersing bryophytes through endozoochory (Wilkinson et al, 2017;Russo et al, 2020). Additional evidence of bryophyte dispersal through endozoochory has been reported in spectacled flying foxes (Pteropus conspicillatus ) (Parsons et al, 2007) and freshwater fish (Boedeltje et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations